CARDIAC ARRHYTHMIAS IN RHEUMATOID ARTHRITIS - Yarmatov Suvon Totlibayevich; Ismoilova Sitora Isroilovna; Qo’chqorova Muhlisa Zafarovna; Khamidov Jasur Bakirovich (Journals Park Publishing, 2023)
35 patients (82% of women) with an established reliable diagnosis of rheumatoid arthritis (RA) according to the criteria of the ARA were examined, the average age was 46.9 ± 1.2 years. Along with general clinical methods, all patients underwent a 2-echocardiogram study and daily monitoring of the Holter ECG (HM). 68.6% have a gray-positive variant of RA. According to 2DECHOCG, pericardial damage was detected in 12.9%, endocardial damage of heart valves - in 32.8% of patients. After Holter monitoring, the presence of ventricular extrasystoles (VES) of high gradations was revealed in 65.7% of cases, among which paired VES occurred in 48.6%, episodes of unstable tachycardia - in 5.7% and early "R on T" - in 11.4% of patients. At the same time, there were no clinical signs of angina and/or episodes of pain-free myocardial ischemia. A clear trend has been demonstrated in the increase in the number of ventricular arrhythmias of high gradations in combination with damage to the endocardium of the heart valves and/or pericardium with an increase in RA activity, which illustrates the inflammatory nature of heart damage and reflects the subclinical course of rheumatoid carditis. The obtained results demonstrate polymorphism of clinical and instrumental signs of rheumatoid heart disease, which significantly complicates its timely diagnosis.
Keywords: rheumatoid arthritis, heart, arrhythmias, inflammation.